A bibliometric review of positive psychology and well-being research in Africa - Fadiji, Angelina Wilson; Khumalo, Itumeleng P.; Wissing, Marié Philipina; Appiah, Richard (Frontiers in Psychology, 2024)
Positive Psychology rapidly developed into an influential field of study and intervention, initially situated in Psychology, and later becoming multidisciplinary. Research interest in the study of (psychological) well-being has gained global popularity, with increasing salience in Africa. Although the global trends of these developments are relatively well-known, a bibliometric analysis of positive psychology research in Africa was necessary to shed light on the present hotspots and trends and future trajectories in this region of the world. The data source of the present bibliometric analysis study was Scopus, from which Positive Psychology and well-being research literature from Africa between 1983 and 2023 were searched. Using biblioshiny and VOSviewer, the 622 extracted articles were analysed, from which findings about the current condition, research hotspots, and thematic developmental patterns could be made. Africa experienced an initial slow growth period from 1983 until 2005, after which a rapid growth in research productivity, relevance and impact was experienced. In this regard, the results show that the focal point of scientific productivity is South Africa, with the dominance of South African institutions, particularly the North-West University, from where most positive psychology research is produced and cited. Even with potential access to international journal, African researchers seem to prefer to place their publications in the regional journals such as Journal of Psychology in Africa and South African Journal of Psychology. The research reviewed tends to be characterised by more dominant thematic clusters of positive psychology, psychological well-being, and subjective well-being, with a focus on human individuals. An increasing concern for contextual factors and potential antecedents and dynamics of well-being is also observed. The findings provide a good map from which identification of future research priorities can be deduced. As such, we speculate that future positive psychology research in Africa ought to be concerned with the following: greater distribution and intercountry collaborations across the continent, questions of conceptual clarity of terms, better understanding of contextual factors which influence well-being, and well-being research embracing the complexity of bio-psychosocial-ecological well-being, and science concerned with health-promotion interventions.